26 Case Report of a Pseudoaneurysm from Distal Anastomosis of Open AAA 32 Years Previously, Contained Within Original Aortic Sac. (19th August 2022) - Clelland, A; Sravanam, S; Chatha, S; Metcalfe, M
Abstract: An 86-year-old gentleman attended hospital with confusion following collapse at home. On examination the abdomen was soft, non-tender and distended with an expansile mass. He underwent elective open repair of a 7cm AAA 32 years prior to current presentation. His past medical history included severe aortic stenosis and atrial fibrillation for which he was anticoagulated with warfarin. CT imaging of head for intracranial pathology. Triple phase contrast CT studies to assess possible aortic pathology. CT brain excluded intracranial pathology as cause of collapse. CT triple phase aortogram demonstrated an 8.4cm infrarenal abdominal aortic aneurysm. Arterial phased images show contrast in the previous aortic repair, however delayed images showed extravasation of contrast from a potential leak at the distal suture line, with blood filling the original aortic sac, outside the aortic surgical graft. No retroperitoneal leak was identified. This presentation was amenable to relining of the aorta with an EVAR however given the patient was asymptomatic and had significant comorbidities, no further intervention was undertaken. The patient and family agreed with this plan of action, and the patient died 3 weeks later. The duration of this contained leak was unknown.